ANALISIS KESULITAN MEMBACA SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS 2B DI SDN 04 TENGGULITAHUN PELAJARAN 2023-2024 - Elis Elis; Mujahidin Mujahidin; Parni Parni (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The aim of this research is to reveal, 1) to find out students' reading difficulties in class 2B Indonesian language lessons at SDN 04 Tengguli for the 2023-2024 academic year, 2) to describe the teacher's way of overcoming students' reading difficulties in class 2B Indonesian language lessons at SDN 04 Tengguli for the 2023-2024 academic year, 3) determine the supporting and inhibiting factors for students' reading difficulties in class 2B Indonesian language lessons at SDN 04 for the 2023-2024 academic year. This research uses descriptive research with a qualitative approach. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data display and conclusion drawing. The results of this research show that; 1) Students' reading difficulties in class 2B Indonesian language subjects at SDN 04 Tengguli for the 2023-2024 academic year are errors in identifying letter sounds, incorrect reading direction habits, weaknesses in comprehension abilities, personal difficulties with types of reading, and weaknesses in reading speed, such as not yet fluent in reading, difficulty distinguishing letters, often halting spelling, difficulty stringing letters into words well. 2) The teacher's way of overcoming students' reading difficulties in class 2B Indonesian language lessons at SDN 04 Tengguli for the 2023-2024 academic year, namely selecting and determining strategies that the teacher will use to overcome reading difficulties experienced by students, selecting and determining students' learning media, select and determine teaching and learning methods and techniques that are considered to be the most effective. 3) The supporting factors and inhibiting factors for students' reading difficulties in class 2B Indonesian language lessons at SDN 04 Tengguli for the 2023-2024 academic year are that adequate facilities and infrastructure tend to produce maximum reading learning and maximum understanding, and vice versa, facilities and Inadequate school infrastructure will hamper the process of learning to read at school.